Концепти часу в «Camera lucida» Р. Барта: літературознавчі проекції - Лавринович, Лілія; Lavrynovych, Lіliya (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті проаналізовано особливості впливу фото як візуального засобу комунікації / відтворення на новітню літературу, зокрема на темпоральні аспекти літературно-художньої практики. Через феноменологію фото, відбиту в книзі Р. Барта «Camera lucida», досліджено такі аспекти поетики літературного твору, як надмірна увага до візуальної фіксації миті, кореляція візуального та текстового в меморіальному, феномен часових інверсій, спаціалізація, принцип тиражування / множення в поетиці часу тощо. The peculiarities of impact of the photography as visual means of communication / reproduction on modern literature, in particular temporal aspects of the literary and artistic practice have been analysed in the article. Such aspects of the poetics of the literary work as the excessive attention to visual fixation of the moment, correlation between visual and textual within commemorative, phenomenon of temporal inversions, spacialisation, the principle of replication / multiplication in the poetics of time have been investigated through the prism of photo phenomenology, reflected in R. Barthes’ book “Camera lucida”.The peculiarities of impact of the photography as visual means of communication / reproduction on modern literature, in particular temporal aspects of the literary and artistic practice have been analysed in the article. Such aspects of the poetics of the literary work as the excessive attention to visual fixation of the moment, correlation between visual and textual within commemorative, phenomenon of temporal inversions, spacialisation, the principle of replication / multiplication in the poetics of time have been investigated through the prism of photo phenomenology, reflected in R. Barthes’ book “Camera lucida”.
Time Concepts in «Camera lucida» by R. Barthes: Literary Projections
Keywords: фото; поетика часу; «Camera lucida»; «візуальний поворот»; художня література ХХ ст.; photo; poetics of time; “Camera lucida”; “visual turn”; belles-lettres of the XXth century